2020
DOI: 10.1002/jper.20-0126
|View full text |Cite
|
Sign up to set email alerts
|

Validation in a Brazilian population of gene markers of periodontitis previously investigated by GWAS and bioinformatic studies

Abstract: Background: Bioinformatic tools and genome-wide association studies (GWAS) have led to comprehensive identification of single nucleotide polymorphisms (SNPs) associated with periodontitis in diverse populations. Here we aimed to detect and validate the association of seven SNPs as genetic markers of susceptibility to periodontitis in a Brazilian population. Methods: This case-control study assessed complete periodontal parameters of 714 subjects with periodontal status classified as healthy/mild periodontitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In the first, rs3811046 was linked with severe chronic periodontitis (OR = 1.50), 10-year incident tooth loss (relative risk = 1.33) and aggressive periodontitis (OR = 1.12) in German/Dutch adults (Offenbacher et al, 2018). In a more recent study, it has been demonstrated that rs3811046 was associated with an increased risk of developing moderate periodontitis (OR = 2.58) in a Brazilian population (Cirelli et al, 2021). In Graves' disease, the rs3811046 variant was significantly associated with a decreased risk in female patients (OR = 0.777) (Yan et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…In the first, rs3811046 was linked with severe chronic periodontitis (OR = 1.50), 10-year incident tooth loss (relative risk = 1.33) and aggressive periodontitis (OR = 1.12) in German/Dutch adults (Offenbacher et al, 2018). In a more recent study, it has been demonstrated that rs3811046 was associated with an increased risk of developing moderate periodontitis (OR = 2.58) in a Brazilian population (Cirelli et al, 2021). In Graves' disease, the rs3811046 variant was significantly associated with a decreased risk in female patients (OR = 0.777) (Yan et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…We used the answers to classify them as never-smokers or ever-smokers (current smokers + former smokers). Regarding smoking status, participants were classified as a smoker when they reported smoking on a daily basis for at least one year with a mean of 20 cigarettes per day, and a former smoker when they had stopped smoking for at least one year [ 16 , 51 ]. Each participant also self-reported their skin color, as white (67.4%), black (10.83%), brown (19.31%) or mulatto (2.46%).…”
Section: Methodsmentioning
confidence: 99%
“…Each participant also self-reported their skin color, as white (67.4%), black (10.83%), brown (19.31%) or mulatto (2.46%). We assessed the clinical periodontal parameters—interproximal probing pocket depth (PPDi), interproximal clinical attachment level (CALi), bleeding on probing (BOP), the visible plaque index, and marginal bleeding—by utilizing a University of North Carolina-15 periodontal probe at four sites (interproximal sites) around each tooth [ 16 , 17 , 51 ]. We followed the Centers for Disease Control and Prevention/American Academy of Periodontology (CDC/AAP) criteria to define periodontitis [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete periodontal examination of all subjects assessed the following clinical signs and parameters at four interproximal sites around each tooth: probing pocket depth (PPDi) and clinical attachment level (CALi), measured to the nearest millimeter by a UNC-15 periodontal probe (Millennium®) and the presence of visible plaque, marginal bleeding and bleeding on probing (BOP) [ 32 , 33 ]. The last three parameters were registered as a percentage of the total number of interproximal sites assessed.…”
Section: Methodsmentioning
confidence: 99%